2017
DOI: 10.5489/cuaj.4097
|View full text |Cite
|
Sign up to set email alerts
|

Shock due to urosepsis: A multicentre study

Abstract: Introduction: Urosepsis is a severe infection that can cause shock afterwards. The purpose of this study is to investigate the clinical and bacterial risk factors for shock in those cases with urosepsis caused by urinary tract infection in a multicentre study. Methods: Our study included 77 consecutive urosepsis cases from four hospitals. We examined factors such as patient characteristics, underlying disease, serum white blood cell (WBC) count, platelet count, C-reactive protein (CRP) level at the time of dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
(26 reference statements)
1
11
0
Order By: Relevance
“…found that frequently isolated causative bacteria for urosepsis or bacteremic UTI other than E. coli with or without ESBL‐producing bacteria included Proteus species, Enterococcus species, Klebsiella species, other Gram‐positive cocci and P. aeruginosa . In the present study, we showed that clinical risk factors for death associated with P. aeruginosa ‐causing bacteremia included the isolations of Klebsiella pneumoniae , Staphylococcus aureus or Staphylococcus epidermidis . However, as aforementioned, our comparatively high mortality rate (14.5%) from P. aeruginosa urosepsis required particular attention.…”
Section: Discussionsupporting
confidence: 38%
See 2 more Smart Citations
“…found that frequently isolated causative bacteria for urosepsis or bacteremic UTI other than E. coli with or without ESBL‐producing bacteria included Proteus species, Enterococcus species, Klebsiella species, other Gram‐positive cocci and P. aeruginosa . In the present study, we showed that clinical risk factors for death associated with P. aeruginosa ‐causing bacteremia included the isolations of Klebsiella pneumoniae , Staphylococcus aureus or Staphylococcus epidermidis . However, as aforementioned, our comparatively high mortality rate (14.5%) from P. aeruginosa urosepsis required particular attention.…”
Section: Discussionsupporting
confidence: 38%
“…6 In the present study, we showed that clinical risk factors for death associated with P. aeruginosa-causing bacteremia included the isolations of Klebsiella pneumoniae, Staphylococcus aureus or Staphylococcus epidermidis. 8 However, as aforementioned, our comparatively high mortality rate (14.5%) from P. aeruginosa urosepsis required particular attention. Other risky bacteria, for instance ESBL-producing E. coli or K. pneumoniae cases, accounted for 41.5% of adults with hospital-acquired urosepsis, but the clinical risk factors for infection-related death from P. aeruginosa should be also monitored in order to reduce mortality.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…CRP and PCT are widely used in clinical practice as important indicators to reflect the degree of inflammation in the body. Fukashi Yamamichi et al 14 analysed on the data of77 patients with urosepsis, suggesting that CRP was the only risk factor for sepsis involving tumor obstructionto progress to septic shock. In contrast to Yamamichi, most scholars believe that PCT is significantly superior to CRP in the diagnostic sensitivity and specificity of severe sepsis and septic shock, and is also superior to CRP in the assessment of the severity and prognosis of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors attributing to septic shock have previously been reported in patients with UTI. Indwelling urinary catheter and increased C-reactive protein levels were risk factors of septic shock in UTI patients with or without bacteremia (18, 21). Our study showed that urolithiasis could be a good predictor of the development of uroseptic shock in UTI patients.…”
Section: Discussionmentioning
confidence: 99%